Estimated Inflation by Household Characteristics - Flannery, Edel; Keating, Joseph (Statistical and Social Inquiry Society of Ireland, 2023)
Price changes, as measured by the Consumer Price Index (CPI) had remained relatively stable for the last number of years, with annual changes in the CPI remaining under +2.0% between September 2012 and June 2021 inclusive. While prices decreased on an annual basis through much of 2020, inflation has been increasing since April 2021 and has been at least 5.0% since October 2021. The annual inflation rate of 9.2% measured in October 2022 is the highest seen since Quarter 2 1984 when annual inflation stood at 9.7%. The increasing rate of inflation since the middle of 2021 has prompted a greater interest in price change and its effect on households. The CPI is designed to measure the annual rate of inflation, i.e. the change in the average level of prices for consumer goods and services. Thus, the CPI is a measure of average inflation, based on average expenditure weights. However, every household has its own unique consumption pattern and therefore its own personal experience of inflation. Households that spend a higher proportion of their total expenditure on goods and services that are increasing in price by more than the rate of inflation, will experience higher inflation than the CPI average rate. While it would not be feasible to calculate inflation for each individual household, research in Ireland and other countries has highlighted the value of compiling inflation estimates for different groups or cohorts of the population. This paper begins by presenting the history of changes in the cost of living in Ireland over the last 100 years and outlines how the drivers of those price changes have evolved over time. It then presents results from the Household Budget Survey (HBS) which can be used to estimate inflation rates for various household groups. Estimated rates of inflation for the five year period up to September 2022 are presented for households grouped by equivalised gross household income deciles, by household tenure, by the location of the household (urban/rural), by the age of the household reference person, and by the composition of the household. Finally, the paper demonstrates how those estimated inflation rates for the various household groups have evolved in the last five years.
Cost of Living Symposium (read before the Society, 8th December 2022)
Keywords: inflation; Ireland; households; expenditure; Consumer Price Index; 314.15